Analytic Blackout Data for the Fully-Compensated Transmission Line (University of Khartoum Engineering Journal, 2022)
This paper presents a case for an analytical solution to the voltage stability of radial power links asdetermined by the maximum power transfer capability limit of a 100% capacitor-compensated transmission line.The prediction method uses an auxiliary circuit with variables that will simulate an active angle stability referencein the conventional sense of steady-state stability limits in radial links; but will not show in the final transfercharacteristics of the source. The algebraic solution evolves in a voltage regulation curve that allows fordimensionless depiction of stability information including voltage limits for the stable transfer of maximumpowers and hence for any powers below these maxima.